Parental Identity and Lived Experiences when Parenting a LGBTQIA+2 Child: A Critical Narrative Synthesis of Current Evidence - Cherryl S. Kolhe; Shirin Shikalgar; Deborah Biggerstaff (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Most LGBTQIA + 2 studies focus on the core sexually and gender diverse population without exploring the peripheral familial perspectives. Current research needs to explore parental experiences of parenting a LGBTQIA+2 child, since parents undergo an identity change after their child’s disclosure. This parental identity change may affect parental well-being and add to the existing stress of parenting a LGBTQIA + 2 child. Methods This paper uses the identity process theory (IPT) to review 18 studies on parental narratives to highlight the change in parental identity. Databases were searched for first-hand parenting experiences and shortlisted articles were qualitatively synthesized. Findings We identified six main themes: I) Parental identity change is triggered by a child’s disclosure. II) Parental identity change drives parental emotions that evolve from initial anger, shock, fear, concern, grief, etc. to eventual acceptance of their child. III) Parental identity and emotions change, as for any life change process, across assimilation, accommodation, adjustment, and evaluation phases of the IPT. IV) Parental identity change is motivated by continuity, coherence, self-efficacy, belongingness, distinctiveness, meaning and self-esteem principles of the IPT. V) Parental identity influences parental micro-individual, meso-interactional and macro-societal interactions of the IPT framework. VI) Parental mental well-being may be affected across the assimilation, accommodation, adjustment phases of the IPT before eventual acceptance of the child in the evaluation phase. Conclusions Parental lived experiences require a stronger consideration today within the wider, non-white, contexts. The effect of identity change on parental mental well-being and its intergenerational effect needs to be explored within the context of the IPT. Parental narratives will contribute towards creating appropriate counselling toolkits and interventions for health care providers and parents of LGBTQIA + 2 children.